Experience Sharing of CGIAR Innovations with PKSF: Workshop Proceedings - International Rice Research Institute (International Rice Research Institute, 2025)
As part of the CGIAR Scaling for Impact program, the International Rice Research Institute (IRRI), in collaboration with Palli Karma-Sahayak Foundation (PKSF), organized a knowledge-sharing workshop on 25 May 2025 in Dhaka, Bangladesh. The workshop aimed to present scalable agricultural innovations developed by CGIAR centers and explore opportunities for collaboration to accelerate their uptake in Bangladesh. Researchers from IRRI, CIMMYT, and CIP showcased innovations related to agronomic practices for coastal polder zones, digital agriculture, diversified cropping systems, zero tillage potato production, and water and climate risk management. PKSF officials expressed interest in selected innovations and discussed pathways for partnership, including joint project development, capacity building, and renewed institutional collaboration through a memorandum of understanding with IRRI. The workshop provided a platform to align CGIAR innovations with PKSF’s development programs, laying the foundation for future collaborative scaling efforts.